Photon‐Pair Generation with a 100 nm Thick Carbon Nanotube Film. Issue 24 (24th April 2017) - Lee, Kim Fook; Tian, Ying; Yang, He; Mustonen, Kimmo; Martinez, Amos; Dai, Qing; Kauppinen, Esko I.; Malowicki, John; Kumar, Prem; Sun, Zhipei
Abstract : Nonlinear optics based on bulk materials is the current technique of choice for quantum‐state generation and information processing. Scaling of nonlinear optical quantum devices is of significant interest to enable quantum devices with high performance. However, it is challenging to scale the nonlinear optical devices down to the nanoscale dimension due to relatively small nonlinear optical response of traditional bulk materials. Here, correlated photon pairs are generated in the nanometer scale using a nonlinear optical device for the first time. The approach uses spontaneous four‐wave mixing in a carbon nanotube film with extremely large Kerr‐nonlinearity (≈100 000 times larger than that of the widely used silica), which is achieved through careful control of the tube diameter during the carbon nanotube growth. Photon pairs with a coincidence to accidental ratio of 18 at the telecom wavelength of 1.5 µm are generated at room temperature in a ≈100 nm thick carbon nanotube film device, i.e., 1000 times thinner than the smallest existing devices. These results are promising for future integrated nonlinear quantum devices (e.g., quantum emission and processing devices). Abstract : Correlated photon pairs are generated, with a coincidence to accidental ratio of 18 at the telecom wavelength of 1.5 µm, through spontaneous four‐wave mixing in a ≈100 nm thick carbon nanotube film device at room temperature, which is 10 3 times thinner than the smallest existing devices.